2017
DOI: 10.3390/polym9110562
|View full text |Cite
|
Sign up to set email alerts
|

Towards Flexible Dielectric Materials with High Dielectric Constant and Low Loss: PVDF Nanocomposites with both Homogenously Dispersed CNTs and Ionic Liquids Nanodomains

Abstract: Flexible dielectric materials with high dielectric constant and low loss have attracted significant attention. In this work, we fabricated novel polymer-based nanocomposites with both homogeneously dispersed conductive nanofillers and ion-conductive nanodomains within a polymer matrix. An unsaturated ionic liquid (IL), 1-vinyl-3-ethylimidazolium tetrafluoroborate ([VEIM][BF 4 ]), was first coated on the surface of multi-walled carbon nanotubes (CNTs) by the mechanical grinding. The ILs coated CNTs were then we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…Assuming   16 [10] and taking into account that о  8.8510 -12 Fm -1 and Е  60 MVm -1 in the case of the middle field, we obtained Рcap  0.79 Ccm -2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assuming   16 [10] and taking into account that о  8.8510 -12 Fm -1 and Е  60 MVm -1 in the case of the middle field, we obtained Рcap  0.79 Ccm -2 .…”
Section: Discussionmentioning
confidence: 99%
“…6 -Schematic of the processes occurring in PVDF poled in the middle fields, at the moment of short-circuiting (a), the distribution of the field strength at the moment of shortcircuiting (b), and the state of the sample after aging in the short-circuited state charges located either on the electrode or in the near-surface layer injection of charge carriers from electrodes in the formation of polarized zones in PVDF. The concept of the close interrelation between trapped charges and the ferroelectric polarization in PVDF was suggested and proved in several publications [7][8][9][10]. Experimental data indicated that in the case of widely used Al electrodes, the level of injection from the negative metal electrode was higher than from the positive electrode.…”
Section: Discussionmentioning
confidence: 99%
“…Two main strategies have been developed by researchers to enhance the dielectric permittivity [5,6,7,8,9,10,11,12]. One is incorporating ceramic fillers with intrinsically high dielectric constants (e.g., BaTiO 3 , Ba x Sr 1-x TiO 3 , CaCu 3 Ti 4 O 12 ) [13,14,15,16,17,18,19,20] into the polymer matrix; the other strategy is employing conductive fillers, including metals (e.g., Ag, Ni, Al) [21,22,23,24,25], carbon materials (e.g., carbon nanotubes, graphene) [26,27,28,29,30,31,32], semiconductors (e.g., ZnO) [33], and conductive polymers (e.g., polyaniline (PANI)) [34,35,36,37]. With ceramic/polymer composites, the merits of high ε r from ceramic fillers and high breakdown strength from polymers are combined.…”
Section: Introductionmentioning
confidence: 99%
“…Dielectric materials have attracted great attention due to their uses in energy storage applications. Among a variety of physical properties, such as high dielectric constant, low dielectric loss and high electric breakdown strength are the mainly significant parameters that offer valuable information concerning the dielectric materials 1 . The demands for polymer materials have progressively increased with the advancement of science and technology.…”
Section: Introductionmentioning
confidence: 99%